2012
DOI: 10.1016/j.joca.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Hylan G-F 20 maintains cartilage integrity and decreases osteophyte formation in osteoarthritis through both anabolic and anti-catabolic mechanisms

Abstract: Hylan G-F 20 improved cartilage integrity and decreased osteophyte formation in the rabbit model of OA. Our results suggest that hylan G-F 20 may stimulate cartilage repair by increasing Col II, and inhibit IL-1β-mediated matrix degradation by decreasing MMPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 47 publications
4
22
0
3
Order By: Relevance
“…Pro-Hyp also stimulates the production of hyaluronic acid by cultured synovial cells (12,28). Notably, hyaluronic acid exhibits anti-inflammatory action (29). Based on these findings, it is tempting to speculate that Pro-Hyp, which is derived from orally administered CP, enhances the production of hyaluronic acid and glycosaminoglycans by synovial cells and chondrocytes, thereby exhibiting anti-inflammatory and chondroprotective actions (as evidenced by the suppression of MMP-13 expression, type II collagen degradation and morphological changes) in vivo in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-Hyp also stimulates the production of hyaluronic acid by cultured synovial cells (12,28). Notably, hyaluronic acid exhibits anti-inflammatory action (29). Based on these findings, it is tempting to speculate that Pro-Hyp, which is derived from orally administered CP, enhances the production of hyaluronic acid and glycosaminoglycans by synovial cells and chondrocytes, thereby exhibiting anti-inflammatory and chondroprotective actions (as evidenced by the suppression of MMP-13 expression, type II collagen degradation and morphological changes) in vivo in our model.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that inflammation-induced PGE 2 and NO concentrations could be suppressed by hylan G-F 20 [42]. Hylan G-F 20 can also interact with membrane receptor CD44 and intracellular adhesion molecule-1 (ICAM-1) for modulating the inflammatory effects, including inhibiting the IL-induced matrix-degrading enzymes and production of proinflammatory mediator, and also preventing cell apoptosis [43]. Collectively, hylan G-F 20 could potentially be further used for BPH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects were also found in comparison with patients without treatment (Bjørnland et al, 2007;Møystad et al, 2008); and no differences were found with the short-term use of intraarticular corticosteroids (Guarda-Nardini et al, 2005;Manfredini et al, 2010). However, the use of corticosteroids can present some adverse effects such as progression of the disease and condylar resorption (Wenneberg et al, 1991;El-Hakim et al, 2005), whereas the application of EHA does not show any major adverse effects (Li et al, 2012;Grossmann et al, 2013). According to Uchôa de Rezende & Constantino de Campos, the minimum adverse effects described were related to the infiltration procedure, such as effusion, joint pain, burning and joint erythema, which are all temporary.…”
Section: Characteristics Of the Temporomandibular Jointmentioning
confidence: 99%